Southeast view of jangha (wall) of the Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
The southeast profile of the Kaner-ki-Putli Temple exhibits the elevation with the vedibandha (basal mouldings) and jangha (wall). The latter displays the projected and recessed sections, embellished with figurative decorations. The shikhara (superstructure), however dilapidated, is of the Bhumija style.